2018
DOI: 10.1021/acsami.8b01658
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Prodrug Therapy Achieves Site-Specific, Personalized Physiological Responses to the Locally Produced Nitric Oxide

Abstract: Nitric oxide (NO) is a highly potent but short-lived endogenous radical with a wide spectrum of physiological activities. In this work, we developed an enzymatic approach to the site-specific synthesis of NO mediated by biocatalytic surface coatings. Multilayered polyelectrolyte films were optimized as host compartments for the immobilized β-galactosidase (β-Gal) enzyme through a screen of eight polycations and eight polyanions. The lead composition was used to achieve localized production of NO through the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 45 publications
(84 reference statements)
1
30
0
Order By: Relevance
“…Alternatively, surface modification can be designed to be virtually permanent, using non-degradable polymers. In our prior studies, we engineered EPT into multilayered polyelectrolyte coatings to achieve localized synthesis of anti-proliferative drugs [ 22 ] and for delivery of nitric oxide [ 15 ], biomedical opportunities highly warranted in the context of cardiovascular stenting. We have also demonstrated that enzymes immobilized within such coatings exhibit negligible escape from the multilayered films and biocatalysis is confined to the surface coatings, being key to the desired site-specific production of therapeutics via EPT.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, surface modification can be designed to be virtually permanent, using non-degradable polymers. In our prior studies, we engineered EPT into multilayered polyelectrolyte coatings to achieve localized synthesis of anti-proliferative drugs [ 22 ] and for delivery of nitric oxide [ 15 ], biomedical opportunities highly warranted in the context of cardiovascular stenting. We have also demonstrated that enzymes immobilized within such coatings exhibit negligible escape from the multilayered films and biocatalysis is confined to the surface coatings, being key to the desired site-specific production of therapeutics via EPT.…”
Section: Resultsmentioning
confidence: 99%
“…We have also demonstrated that enzymes immobilized within such coatings exhibit negligible escape from the multilayered films and biocatalysis is confined to the surface coatings, being key to the desired site-specific production of therapeutics via EPT. [ 15 , 22 , 40 ] Herein we propose that such nanometer-thin coatings can be deposited on the surface of an implant to prevent and/or treat bacterial biofilm ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past tens of years, nitric oxide delivery carriers have developed into various biomedical application forms, such as nanoparticles, [1][2][3][4] thin lm coatings, 5,6 hydrogels, 7,8 metalorganic frameworks (MOFs). 9,10 Nitric oxide (NO) is an indispensable cell signaling gas molecule, which is generated by nitric oxide synthases (NOSs) by consuming L-arginine.…”
Section: Introductionmentioning
confidence: 99%